Ultrasonic emulsification to facilitate mitral valve reconstruction in mitral annular calcification - Rheault-Henry, Mathieu; Malik, Mohsyn Imran; Bhatt, Nitish; Gelinas, Jill; Chu, Michael W. A. (Annals of Cardiothoracic Surgery; Vol 14, No 6 (November 30, 2025): Mitral Annular Calcification, 2025)
Background: Mitral annular calcification (MAC) increases the complexity and risk of mitral valve surgery, often limiting repair feasibility. This study evaluates the early outcomes of ultrasonic emulsification and aspiration using a novel device to facilitate mitral valve repair. Methods: We conducted a prospective, single-centre, single-surgeon series of 27 consecutive patients with moderate-to-severe MAC and degenerative mitral regurgitation (MR) undergoing Sonopet-assisted decalcification between June 2023 and July 2025. Procedures were performed via median sternotomy or endoscopic mini-thoracotomy. Ultrasonic aspiration was used to remove and sculpt MAC, enabling annular remodelling and secure repair. The primary outcome was repair success and residual regurgitation; secondary outcomes included mortality and perioperative complications. Results: Mitral repair was successfully performed in 26 patients (96.3%), with one conversion to replacement. There were no in-hospital deaths, strokes, atrioventricular (AV) groove disruptions, or reoperations. At discharge, 96.3% had none or mild residual MR; one patient (3.7%) had moderate MR. Mean coaptation length was 10.3±3.2 mm. Postoperative complications included new-onset atrial fibrillation in five patients (18.5%) and permanent pacemaker implantation in two (7.4%). Sternotomy approach was used in 63% and endoscopic mini-thoracotomy in 37%. Mean cardiopulmonary bypass (CPB) and cross-clamp times were 159.6±46.8 and 116.9±46.5 min, respectively. Most mitral repairs addressed isolated posterior leaflet prolapse (66.7%) or bileaflet prolapse (22.2%). Primary repair strategies included leaflet resection (51.9%), isolated neochords (25.9%), or resection with neochords (22.2%). MAC decalcification was primarily performed in the posterior annulus. Conclusions: Ultrasonic emulsification is a safe, effective adjunct for mitral valve repair in moderate-to-severe MAC, enabling precise decalcification and high repair rates with minimal complications. This approach may expand repair candidacy and merits further comparative studies with long-term follow-up.